THE INFLUENCE OF CORPORATE IMAGE, SERVICE QUALITY, PERCEIVED VALUE TOWARD STUDENT SATISFACTION AND STUDENT LOYALTY - Gatri Lunarindiah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
Student satisfaction and student loyalty are important factors in business education. This research was conducted with the goal to test and analyze the influence of corporate image, service quality and perceived value on student satisfaction and student loyalty. The object of the sample is students of the Economics and Business Faculty of Trisakti University as many as 150 respondents and the analysis was done by using the method of Structural Equaton Model (SEM) producing conclusion that the corporate image, service quality and perceived value proved to be positive and significantly influential upon student satisfaction and service quality also proved to have a positively significant effect on student loyalty. There is a hypothesis that student satisfaction is not proven positively influencial upon student loyalty.